EFEKTIVITAS ANTI-NYAMUK BAKAR ALAMI BERBAHAN TANGKAI BUNGA CENGKEH (Syzygium aromaticum L. Merr. & L.M. Perry) SERTA PERSEPSI MASYARAKAT TERHADAP PEMANFAATANNYA - Dharmawaty M Taher; Yuyun Muhammad; Bahtiar Bahtiar; Syamsul Bahri; Febri Ayu (JURNAL BIOEDUKASI, 2025)
Clove flower stalks (Syzygium aromaticum L. Merr. & Perry) are agricultural waste containing eugenol compounds, which have the potential to be natural active ingredients in mosquito repellent products. This study aims to describe the formulation process of mosquito repellent made from clove flower stalks, evaluate the effectiveness of burning time, and analyze public perception of its use. The method used is descriptive quantitative. The product is formulated from a mixture of clove flower stalk powder, adhesive (joss powder), and water with a ratio of 20 g: 6 g: 40 mL, molded in a spiral shape, and dried for 2-3 days. The resulting product has a dark brown color, a distinctive clove aroma, a smooth texture, a spiral length of 65 cm, a diameter of 11 cm, and an average weight of 21 grams, resembling the shape of synthetic mosquito repellent. The average burning time reaches 9.3 hours. Public perception of this product is relatively positive, especially in terms of aroma, color, and effectiveness in repelling mosquitoes. These findings indicate that clove flower stalks have the potential to be an alternative raw material that is effective, environmentally friendly, and acceptable to the community in the development of natural mosquito repellent products.